Analisis Pengaruh Kecerdasan Emosional Terhadap Tingkat Pemahaman Akuntansi Dimoderasi Oleh Kepercayaan Diri (Students' Journal of Accounting and Banking, 2012)
The purpose of this study was to obtain empirical evidence of whether the emotional intelligence of students affect the level of understanding of accounting with confidence as a moderating variable. Population taken in this study were students of Economics, University of accounting faculty Stikubank Semarang. The sample in this study using purposive samplingThis research method is used to test the hypothesis in this study is to use multiple linear regression and regression with moderating variables, hypothesis checking is done by mengumpulkjan answers from 60 respondents to the criteria the student has to take introductory accounting courses 1, 2 introductory accounting, financial accounting intermediate 1, intermediate 2 financial accounting, accounting information 1, 2 advanced accounting, auditing 1, 2 auditing, and accounting theory.Based on the results of this study assert that emotional intelligence (self-knowledge, self-control, motivation, empathy and social skills) significantly influence the level of accounting understanding, and confidence to have influence as a moderating variable Keywords: self-knowledge, self-control, motivation, empathy, social skills, and confidence.